Head injuries in the accident and emergency department: are we using resources effectively? - Wallace, S A (1994)
This paper reports a retrospective criterion based audit which reviewed head injury management in two accident and emergency (A&E) departments. Management was compared with regionally agreed criteria for ordering a skull radiograph (SXR) and a computerized tomogram (CT scan) and for admission, and the quality of medical documentation was assessed. A total of 158 patients were reviewed and 132 patients (84%) satisfied the three key areas of recommended head injury management. Failures to satisfy recommended guidelines were present in 19 patients (12%) for SXR, four (2%) for admission and three (2%) for CT scanning. Three skull fractures (two in young babies) would have been missed if the criteria had been adhered to strictly. There was one adverse outcome when a patient who should have been admitted returned to A&E 8 days after initial attendance with a subdural haemorrhage and died shortly afterwards. Apart from 'loss of consciousness', the quality both in content and legibility of the medical documentation was poor. The result of 84% correctly managed patients may be over-optimistic according to the criteria used. Although criteria have a valuable role to play, there are problems with prescriptive standard setting. A recommendation was made to develop a head injury pro forma to address the poor quality medical documentation and it was also recommended that the SXR, CT scan and admission criteria for babies and young children be reviewed.